Psychological Well-Being of Gifted Teenagers with Different Levels of Creativity - Laktionova, E.B.; Gretsov, A.G.; Orlova, A.V.; Tuzova, A.S. (Psihologičeskaâ nauka i obrazovanie, 2021)
The article substantiates and verifies the hypothesis of the relationship between psychological well-being of gifted teenagers and the features of their creativity.It considers the specifics of psychological well-being in gifted adolescents with different levels of creativity, their attitude to the educational environment, the level of satisfaction with its significant characteristics and the degree of protection from psychological violence.The study was conducted on a sample of students of grades 8—10 of schools specializing in mathematics and natural science.The total number of subjects was 253 students aged 14—17 years (154 boys, 99 girls).The study used the following techniques: the Psychological Well-Being Scale by С.Ryff, the Ingenuity and Divergent Thinking scales from H.Zivert’s test of verbal creativity, and the questionnaire “Psychological Safety of Educational Environment” by I.A.Baeva.The differences in psychological well-being indicators for adolescents with different levels of verbal creativity were identified: in particular, adolescents with high creativity have a lower indicator of “positive relationships with others”.The structure of correlations between psychological well–being and creativity in groups of adolescents with high and low creativity differs.Highly creative gifted teenagers tend to evaluate their condition as less favourable as compared to their peers with low creativity and struggle with establishing close relationships.Adolescents with low creativity are more satisfied with such characteristics of educational environment as relationships with others and opportunities provided by the environment.Their assessment of protection from psychological violence is negatively correlated with originality of thinking. Обосновывается и проверяется гипотеза о взаимосвязи психологического благополучия одаренных подростков и характеристик их креативности. Рассматривается специфика психологического благополучия одаренных подростков с разным уровнем креативности, их отношение к образовательной среде, уровень удовлетворенности ее значимыми характеристиками и степень защищенности от психологического насилия во взаимодействии. Использована методика «Шкала психологического благополучия» К. Рифф, а также шкалы «Находчивость» и «Дивергентное мышление» теста вербальной креативности Х.Зиверта и методика И.А. Баевой «Психологическая безопасность образовательной среды школы». Исследование проведено на выборке учащихся 8—10-х классов специализированных школ математической и естественно-научной направленности. Всего 253 учащихся в возрасте 14—17 лет (154 юноши, 99 девушек). Установлены различия показателей психологического благополучия у подростков с разным уровнем выраженности вербальной креативности: в частности, у подростков с высокой креативностью ниже показатель «положительные отношения с другими». Различается структура взаимосвязей психологического благополучия и креативности в группах высоко- и низкокреативных подростков. Высококреативные одаренные подростки оценивают свое состояние как менее благополучное по сравнению с низкокреативными и испытывают затруднения в выстраивании близких, доверительных отношений. Подростки с низкой креативностью более удовлетворены такими характеристиками образовательной среды, как взаимоотношения с окружающими и предоставляемые средой возможности, оценка защищенности от психологического насилия у них отрицательно связана с оригинальностью мышления.